Txting across time: undergraduates' use of 'textese' in seven consecutive first-year psychology cohorts. Issue 1 (2nd January 2017) - Kemp, Nenagh; Grace, Abbie
ABSTRACT: Communicating by text message is an everyday occurrence for most young adults. This form of communication is often associated with an abbreviated, unconventional spelling style, sometimes called 'textese'. In this study, we report on the changing written language of text messaging, across seven cohorts of first-year Psychology undergraduates ( n  = 728) at an Australian university. From 2009 to 2015, the decline of textese use has gradually tailed off, but remains to represent approximately 12% of written words. Earlier attempts to reduce the number of characters (e.g., for ) are now equalled by emotionally expressive spellings that increase the number of characters (e.g., ), and women have continued to use more textese than men. It appears that today's larger phone screens and keyboards, and easier input methods, rather than any changes in views on the appropriateness of using textese, are the main drivers in reducing young adults' tendency to use unconventional spellings in their text messages.